Upaya Penyuluhan Siber Pada Penyuluh Agama Kota Semarang Pada Masa Pandemi - Ulin Nihayah (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Religious counselor are extension workers who carry out counseling in religious language where the counseling carried out is the implementation of national development. Changes in performance and extension services during the pandemic shifted to using cyber media, where cyber media is media related to computer and information systems with information dissemination in the implementation of the extension carried out. The research conducted by the author is using exploratory qualitative, where the author wants to find cyber counseling efforts carried out by the Semarang City Religious Counselor. The results of the research conducted showed that the implementation of information dissemination carried out by religious instructors was carried out in three ways including: 1. Face-to-face media by visiting the Ministry of Religion or the local KUA, 2 Cyber media through the Ministry of Religion website and YouTube media in the dissemination of information carried out and 3. Blended in counseling services carried out with the community through social media. Cyber extension efforts carried out by religious counselor have not been optimal as for the causes including: 1. The implementation of cyber counseling is self-taught and has not been coordinated and has become part of the extension innovation, 2 Lack of extension resources, 2 Limited skills possessed by extension workers because they are still limited in task performance administrative